2022
DOI: 10.1002/jsfa.12216
|View full text |Cite
|
Sign up to set email alerts
|

Modification of wine phenolic profiles by gibberellic acid application in ‘Cabernet Gernischt’ grapevines before anthesis

Abstract: BACKGROUND Vitis vinifera L. ‘Cabernet Gernischt’ grapes from the Yantai wine region of China usually form dense clusters and contain low phenolic content. We applied five concentrations (ranged from 5 to 25 mg L−1) of gibberellic acid (GA3) to ‘Cabernet Gernischt’ before anthesis to decrease cluster compactness in two consecutive vintages. Yield indices, grape maturity, and wine phenolic compounds were determined. RESULTS GA3 application significantly reduced cluster compactness, bunch weight, and yield per v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Besides, the results of some studies showed that the spraying of different concentrations of GA 3 significantly improved the quality of garlic and Welsh onion; their soluble protein content was significantly higher [7,40]. It was also found that the phenolic content of fruit was significantly higher after GA 3 spraying on 'Cabernet Sauvignon' grapes [41]. 'Nanguo' pear (Pyrus spp) GA 3 soaking retards the decline of ascorbic acid concentration and the increase of total phenolic content of fruits.…”
Section: Gibberellins For Improving the Internal Quality Of Horticult...mentioning
confidence: 99%
“…Besides, the results of some studies showed that the spraying of different concentrations of GA 3 significantly improved the quality of garlic and Welsh onion; their soluble protein content was significantly higher [7,40]. It was also found that the phenolic content of fruit was significantly higher after GA 3 spraying on 'Cabernet Sauvignon' grapes [41]. 'Nanguo' pear (Pyrus spp) GA 3 soaking retards the decline of ascorbic acid concentration and the increase of total phenolic content of fruits.…”
Section: Gibberellins For Improving the Internal Quality Of Horticult...mentioning
confidence: 99%
“…Induced anthocyanin synthesis, caused by GA in petunia (Petunia x hybrida) tissues, was attributed to increased activity of chalcone synthase and chalcone flavanone isomerase [8]. The levels of total phenolic compounds, tannins, and anthocyanins have been altered or increased by GA in grapes (Vitis vinifera L.) in attempts to improve quality [9]. Studies of the effects of GA on antioxidant activity in germinating soybean seeds showed that this compound enhanced the production of antioxidant compounds including phenolics and flavonoids [10].…”
Section: Introductionmentioning
confidence: 99%
“…Spraying gibberellins on P. armeniaca trees could also contribute to the vegetative growth, yield, and quality of fruits (Mohamed, 2019). Further, the application of gibberellins to Vitis trees also increased the fruit setting rate, promoted fruit enlargement, and improved fruit nutrients (Song et al, 2023). As such, spraying gibberellin has become a major method for improving the external and internal quality of fruits in commercial forest crops.…”
Section: Introductionmentioning
confidence: 99%